Occlusions in peripherally inserted central venous catheters in pediatric patients in antineoplastic chemotherapy - Bruna Irene Cunha Curty de Souza; Marcelle Miranda da Silva (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To analyze the occurrence of occlusions in peripherally inserted central venous catheters in pediatric patients in antineoplastic chemotherapy. Method Retrospective cohort, with 156 medical records of patients aged 0-19 years who underwent outpatient chemotherapy between 2013 and 2017 by this catheter, in a hospital in the city of Rio de Janeiro. Descriptive and inferential statistics were applied. Results 219 catheters were registered. Occlusion occurred in 141 (64.4%) catheters; 63 (44.7%) were removed because of occlusion, either alone or associated with another factor. Total occlusion alone led to the removal of 27 (12.3%) catheters. Occlusion was associated with: catheter dwell time, cyclophosphamide, neuroblastoma, bone metastasis and number of chemotherapy sessions. Conclusion Occlusion is an important complication because it occurred in more than half of the catheters and was one of the main reasons for withdrawal. The identified risk factors may guide the care to prevent this complication.